The larva of Amphinemura alabama Baumann and new records of Nemouridae (Plecoptera) from Mississippi, U.S.A - Stark, Bill P. (Illiesia, 2010)
Larvae of Amphinemura alabama Baumann are described and compared with those ofA. nigritta (Provancher), new Mississippi distribution records are given forA. nigritta, Prostoia completa (Walker) and Shipsa rotunda (Claassen), and the first records for A. alabama and Soyedina alexandria Grubbs are presented for the state. An updated checklist of 57 Mississippi stonefly species is included.
Keywords: entomologija; entomology; new species; vrbnice; nove vrste; larval descriptions; Plecoptera; Nemouridae; Amphinemura; Prostoia; Shipsa; Soyedina; Mississippi; USA